Applying an Academic Literacies Lens to the Scholarship of Teaching and Learning (SoTL): A Scoping Review - Dobbins, Kerry (Journal of University Teaching and Learning Practice, 2024)
Scholarship of teaching and learning (SoTL) is central to improving teaching, enhancing students’ learning experiences and ensuring practice is evidence-based. This study explores the insights gained by applying an academic literacies lens to the results of professional development initiatives (programmes, schemes, etc.,) designed to enhance features of faculty colleagues’ SoTL skills. A scoping review was conducted on Journal of University Teaching and Learning Practice (JUTLP) papers published from 2004-2023. Developing teaching practice is a central theme of JUTLP and the papers published across this timeframe provide a rich source from which to explore initial insights as a first step to potentially deeper explorations. The review identified four themes emerging from the qualitative data captured across the review sample: meaning-making together; journey of becoming; flattening of power; and context-specific identities. The analysis points to reasons why collaborative meaning-making opportunities are so valued within professional development initiatives. The academic literacies lens highlights issues of discourse, power, epistemology and identity, and consequently illuminates these collaborative moments as spaces that provide a knowledge and identity-based anchor for colleagues. This lens also stresses the destabilising and emotive nature of ‘becoming’ a pedagogic scholar. Implications of the findings are considered from an academic development perspective. Discussion centres particularly on how academic developers may work to support rather than jeopardise colleagues’ future SoTL trajectories.